Dynamic monocyte changes as prognostic indicators in operable gastric cancer: a retrospective cohort analysis - Jiang, Yiwei; Sun, Xianwei; Yang, Chen; Song, Dandan; Zhou, Chongjun; Chen, Xinxin; Huang, Chongquan; Wang, Zhonglin; Li, Jiante (Frontiers in Oncology, 2025)
ObjectiveThis study aims to elucidate the relationship between postoperative monocyte count and gastric cancer prognosis. We introduce a standardized monocyte ratio (MMR) to predict postoperative survival rates in gastric cancer patients effectively.MethodsA test cohort was created to develop and evaluate the pre- and postoperative MMR as a mortality predictor in gastric cancer patients. We used Kaplan-Meier survival analysis, complemented by univariate and multivariate analyses. The predictive utility of MMR was assessed via time-dependent ROC curves and decision-curve analysis.ResultsThe sample distributions in both cohorts were similar. The MMR showed high predictive value and significant clinical benefits in 1, 3, and 5-year overall survival (OS) assessments. These findings enhance understanding of prognosis and aid in developing more precise treatment plans.ConclusionsMMR is confirmed as an independent factor in predicting overall survival in gastric cancer patients, proving to be a reliable and cost-effective prognostic indicator.